2016
DOI: 10.4102/sajbm.v47i2.62
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Kruger National Park visitors based on interpretation

Abstract: Interpretation is considered to be an important educational tool that not only addresses visitors’ expectations but also contributes to national parks’ conservation purposes. This study segmented the Kruger National Park’s visitors based on expected interpretation services and revealed four clusters that differed based on their expected and experienced interpretation services as well as their motivational aspects. This study’s distinct contribution is the alternative segmentation approach which revealed the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Ham (2013) modified the sequence of EROT to TORE model, to emphasise the importance of a theme embedded in the interpretations. Well‐conceived interpretation programmes have a positive effect on pro‐environmental behaviours, environment‐related interest and awareness of nature (Hvenegaard, 2017) and promote an increased desire to help reduce negative human impacts on the environment (Botha, Saayman, & Kruger, 2016). Effective interactive interpretations tend to evoke a positive emotional response to the conservation of animals and nature and have a significant influence on the memorability of a visitor's experience (Powell & Bullock, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ham (2013) modified the sequence of EROT to TORE model, to emphasise the importance of a theme embedded in the interpretations. Well‐conceived interpretation programmes have a positive effect on pro‐environmental behaviours, environment‐related interest and awareness of nature (Hvenegaard, 2017) and promote an increased desire to help reduce negative human impacts on the environment (Botha, Saayman, & Kruger, 2016). Effective interactive interpretations tend to evoke a positive emotional response to the conservation of animals and nature and have a significant influence on the memorability of a visitor's experience (Powell & Bullock, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of park visitor profiling and segmentation studies can be found in the context of South African national parks (Boshoff et al, 2007; Botha et al, 2016; Kruger et al, 2017; Morrison‐Saunders et al, 2019). For example, Botha et al (2016) used interpretation as a segmentation variable and identified four clusters with their study sample based on the identified interpretation factors. The four clusters are labeled as eager seekers (23%), inquisitive seekers (62%), comfort seekers (10%), and quasi‐interested seekers (5%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The heterogeneous nature of national park tourist behaviors has been acknowledged in the literature as national parks tourist offerings vary widely from wildlife (Boshoff, Landman, Kerley, & Bradfield, 2007) to geological formation and nature‐based attractions (Moyle et al, 2017). Segmentation studies can generally advance the knowledge of park visitor behaviors from different perspectives based on the segmentation methods and criterion variables chosen (Botha, Saayman, & Kruger, 2016). Perceived benefits of visiting national parks appear to be an important and most relevant behavioral construct (Moyle et al, 2014; Moyle & Weiler, 2017), and thus an alternative segmentation variable to better understand national park visitors in a specified context.…”
Section: Introductionmentioning
confidence: 99%
“…If the 14% increase in tourist numbers over the 2016/2017 financial year [23] is any indication to go by the need for sustainable practices is desperately needed for the future. Interpretations link between the tourism and conservation functions of a national park [19].…”
Section: Interpretation and South African National Parksmentioning
confidence: 99%
“…It is perhaps the overnight visitors to the park that contribute financially the most and could therefore be regarded as the main target audience. Botha et al [19], however, found four interpretation market segments for overnight visitors to the park and suggested to focus interpretation developments on the two largest segments (i.e., Inquisitive and Eager seekers). The issue with these two markets, however, is that these two markets require a variety of interpretation services to add to their park experiences.…”
mentioning
confidence: 99%